Lay Person's Esthetic Perception of Black Triangles Using Q -Sort Assessment and Visual Analog Scale - Iftikhar, Ayesha; Khan, Kanza; Shaheed, Sohrab; Ghafoor, Asim (Journal of Indonesian Dental Association, 2025)
Objective: To evaluate the perception of laypersons regarding black triangles between the maxillary central incisors on the esthetics of smile. In addition, we also evaluated the difference between the two grading systems used i.e., Visual analog scale and Q sort assessment. Methods: A picture at smile was manipulated using Photoshop (CC 2019; Adobe Systems) computer program. Black triangles of different sizes were then created between the maxillary central incisors in the embrasure areas. Multiple photographs were generated, and they were evaluated via Visual analog scale and Q sort assessment method by 161 laypersons. Result: The results showed that the larger the black triangle the less attractive the images were rated, regardless of the assessment method used. The presence of no black triangle or a small black triangle (0.5 mm) resulted in the highest scores in both methods. Conclusions: The most attractive image with both assessment methods was the one without any black triangles. Q- sort assessment method is comparable to VAS method in assessing smile esthetics with Laypersons showing consistent agreement in identifying unattractive and attractive smiles. Both assessment methods (VAS scale and Q-sort) showed correlation value=0.9.